Excavations at the former Lauder Technical College, Dunfermline (Proceedings of the Society of Antiquaries of Scotland, 1996)
Excavations revealed a stretch of precinct wall of Dunfermline Abbey -- probably fourteenth-century in date. A medieval corn-drying kiln and a probable nineteenth-century loom stance were also located. There are details of `The pottery' by Robert Will & George Haggarty (1034--6), `Clay tobacco pipes' by Dennis B Gallagher (1036--7), and `Palaeoenvironmental analyses' by Tim Holden, Dorothy Rankin & Alan Duffy (1037--9).